2012
DOI: 10.1186/1471-2261-12-76
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerotic renal artery stenosis is prevalent in cardiorenal patients but not associated with left ventricular function and myocardial fibrosis as assessed by cardiac magnetic resonance imaging

Abstract: BackgroundAtherosclerotic renal artery stenosis (ARAS) is common in cardiovascular diseases and associated with hypertension, renal dysfunction and/or heart failure. There is a paucity of data about the prevalence and the role of ARAS in the pathophysiology of combined chronic heart failure (CHF) and chronic kidney disease (CKD). We investigated the prevalence in patients with combined CHF/CKD and its association with renal function, cardiac dysfunction and the presence and extent of myocardial fibrosis.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…30 RVHT is prevalent in patients with combined congestive heart failure and chronic kidney disease, but its severity does not correlate with LVEF, LVMI, or the extent of myocardial fibrosis. 31 In addition to age, recent cardiovascular or cerebrovascular events, baseline eGFR, and presence of RAS with severe renal dysfunction were independent predictors of mortality. Cherr et al demonstrated increased dialysis-free survival among patients showing improvement in eGFR after renal artery revascularization.…”
Section: Discussionmentioning
confidence: 94%
“…30 RVHT is prevalent in patients with combined congestive heart failure and chronic kidney disease, but its severity does not correlate with LVEF, LVMI, or the extent of myocardial fibrosis. 31 In addition to age, recent cardiovascular or cerebrovascular events, baseline eGFR, and presence of RAS with severe renal dysfunction were independent predictors of mortality. Cherr et al demonstrated increased dialysis-free survival among patients showing improvement in eGFR after renal artery revascularization.…”
Section: Discussionmentioning
confidence: 94%
“…A substantial number of HF patients with CKD exhibit renal artery stenosis. [26] In the present study, no patients with known renal artery stenosis were included, however, there was no formal exclusion. In accordance with relevant previous reports investigating IRD in heart diseases [6,7], in the present study IRD was predominantly performed in the right renal vessels.…”
Section: Discussionmentioning
confidence: 97%
“…Nevertheless, it remains unclear whether atherosclerotic renovascular disease defined as renal artery stenosis >50% might be associated with worsening of cardiac function. Emans et al 2 found that renal artery stenosis is more prevalent in patients with combined chronic heart failure and chronic kidney disease, but it is not correlated with worsening in LVEF, left ventricular volumes and mass or myocardial fibrosis. In a study by de Silva et al 3 renal artery stenosis was associated with an increase in morbidity and mortality in patients with chronic heart failure.…”
Section: Discussionmentioning
confidence: 99%